2019
DOI: 10.3390/app9204362
|View full text |Cite
|
Sign up to set email alerts
|

Extension of an FFT-Based Beam Propagation Method to Plasmonic and Dielectric Waveguide Discontinuities and Junctions

Abstract: We adapted a fast Fourier transform-based Beam Propagation Method (FFT-BPM) to investigate waveguide discontinuities in plasmonic waveguides. The adaptation of the FFT-BPM to treat transverse magnetic (TM) fields requires the circumvention of two major difficulties: the mixed derivatives of the magnetic field and waveguide refractive index profile in the TM wave equation and the step-like index change at the transverse metal-dielectric boundary of the plasmonic guide and the transverse boundaries of the dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Accordingly, the FFT-BPM has been ignored, in spite of its powerfulness, simplicity and accuracy [ 18 ]. Fortunately, [ 19 21 ] the traditional FFT-BPM has been revisited and reformulated to handle TM fields recently. Moreover, this renewed version of the FFT-BPM has been applied to some delicate problem, such as butt-coupling between plasmonic and dielectric waveguide [ 19 , 21 ], and taking into account back-reflected field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the FFT-BPM has been ignored, in spite of its powerfulness, simplicity and accuracy [ 18 ]. Fortunately, [ 19 21 ] the traditional FFT-BPM has been revisited and reformulated to handle TM fields recently. Moreover, this renewed version of the FFT-BPM has been applied to some delicate problem, such as butt-coupling between plasmonic and dielectric waveguide [ 19 , 21 ], and taking into account back-reflected field.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, [ 19 21 ] the traditional FFT-BPM has been revisited and reformulated to handle TM fields recently. Moreover, this renewed version of the FFT-BPM has been applied to some delicate problem, such as butt-coupling between plasmonic and dielectric waveguide [ 19 , 21 ], and taking into account back-reflected field. This motivated us to tackle the problem under the consideration in this research by the novel framework of FFT-BPM as will be shown.…”
Section: Introductionmentioning
confidence: 99%
“…Yra du pagrindiniai būdai sukurti technologinę paklausą atitinkančius sprendimus: naujų struktūrų ir konstrukcijų naudojimas bei medžiagų naudojimas (Saad et al, 2020). Šis poreikis nulemia naujų įtaisų kūrimo ir tyrimo metodų paiešką (Martinez et al, 2019;Shaaban et al, 2019).…”
Section: Bangolaidinės Struktūrosunclassified